Entrepreneurship, innovation, and political competition - Paik, Yongwook; Kang, Sukhun; Seamans, Robert (Strategic Management Journal, 2019)
[Research Summary: With the recent growth of the sharing economy, regulators must frequently strike the right balance between private and public interests to maximize value creation. In this article, we argue that political competition is a critical ingredient that explains whether cities accommodate or ban ridesharing platforms and that this relationship is moderated in more populous cities and in cities with higher unemployment rates. We test our arguments using archival data covering ridesharing bans in various U.S. cities during the 2011–2015 period. We supplement these data with semistructured interviews. We find broad support for our arguments while mitigating potential endogeneity concerns. Our study has important implications for nonmarket strategy, entrepreneurship and innovation, and public-private partnership literatures. In addition, our findings inform policy debates on the sharing economy. Managerial Summary: Entrepreneurs and businesses oftentimes face severe regulatory barriers when commercializing innovative products and services even if the innovations are generally beneficial for consumers and the broader society. This research focuses on the political determinants of regulation to provide a better understanding of why some markets are more receptive to innovative products while other markets are more hostile to them. Using the banning of ridesharing companies (e.g., Uber and Lyft) in various U.S. cities during the 2011–2015 period, we find that elected politicians facing less political competition (i.e., not easily replaceable, serving multiple terms, longer tenure in office) were more likely to ban ridesharing companies and favor, potentially displaceable, local taxicab companies. Our research has implications for navigating the political barriers to entry.]